2010
DOI: 10.1002/jpln.200900201
|View full text |Cite
|
Sign up to set email alerts
|

The evaporation method: Extending the measurement range of soil hydraulic properties using the air‐entry pressure of the ceramic cup

Abstract: Knowledge of hydraulic functions is required for various hydrological and plant‐physiological studies. The evaporation method is frequently used for the simultaneous determination of hydraulic functions of unsaturated soil samples, i.e., the water‐retention curve and hydraulic‐conductivity function. All methodic variants of the evaporation method suffer from the limitation that the hydraulic functions can only be determined to a mean tension of ≈ 60 kPa. This is caused by the limited measurement range of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 15 publications
2
112
0
4
Order By: Relevance
“…Due to cavitation problems when using direct tensiometer measurements, the simplified evaporation method [37] is frequently used for measuring both the SWCC and the suction permeability curve in sands and silts. By using the tensiometer-preconditioning procedure [38], the results were obtained for matric suctions up to 130 kPa. The results obtained from the sample starting from the natural water content are denoted by HYPROP-2.…”
Section: Standard and Volumetric Pressure Plate Extractormentioning
confidence: 99%
“…Due to cavitation problems when using direct tensiometer measurements, the simplified evaporation method [37] is frequently used for measuring both the SWCC and the suction permeability curve in sands and silts. By using the tensiometer-preconditioning procedure [38], the results were obtained for matric suctions up to 130 kPa. The results obtained from the sample starting from the natural water content are denoted by HYPROP-2.…”
Section: Standard and Volumetric Pressure Plate Extractormentioning
confidence: 99%
“…Considering that vegetation mainly consisted of herbaceous plants, an average value of albedo of 0.23 was assumed in calculations of net short-wave radiation (Breshears et al, 1997 ]. In order to reduce the dimensionality of the optimization problem, the soil hydraulic properties of the soil substrate were measured in the laboratory using a simplified evaporation method with an extended measurement range (down to À9000 cm), as proposed by Schindler et al (2010aSchindler et al ( , 2010b. For a detailed description of the modified evaporation method, please refer to Schindler et al (2010aSchindler et al ( , 2010b.…”
Section: Stormwater Filter and Site Descriptionmentioning
confidence: 99%
“…In order to reduce the dimensionality of the optimization problem, the soil hydraulic properties of the soil substrate were measured in the laboratory using a simplified evaporation method with an extended measurement range (down to À9000 cm), as proposed by Schindler et al (2010aSchindler et al ( , 2010b. For a detailed description of the modified evaporation method, please refer to Schindler et al (2010aSchindler et al ( , 2010b. Peters and Durner (2008) conducted a comprehensive error analysis of the simplified evaporation method and concluded that it is a fast, accurate, and reliable method to determine soil hydraulic properties in the measured pressure head range, and that the linearization hypothesis introduced by Schindler (1980) causes only small errors.…”
Section: Stormwater Filter and Site Descriptionmentioning
confidence: 99%
“…The substrate water retention curve (pF curve) and the unsaturated hydraulic conductivity function (K-function) were measured simultaneously using the Extended Evaporation Method (EEM, Schindler et al, 2010) and the HYPROP device (HYdraulic PROPerty Analyser). The measurement was executed on 250cm -3 substrate samples taken in steel cylinders.…”
Section: Hydraulic Measurementsmentioning
confidence: 99%
“…The unsaturated hydraulic conductivity (K) is calculated according to the Darcy-Buckingham law. Using new cavitation tensiometers and applying the air entry value of the tensiometers' ceramic cup allows the range to be extended almost up to the wilting point (Schindler et al, 2010). Fig.…”
Section: Hydraulic Measurementsmentioning
confidence: 99%